Geopolymer-based lightweight fireproof material

A geopolymer-based fireproof material with specific filler and aggregate compositions addresses cracking and deformation issues, ensuring effective fireproofing for steel structures by resisting heat-induced deformation.

JP7602227B2Active Publication Date: 2024-12-18YAMAGUCHI UNIV +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021014630
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-01
Publication Date
2024-12-18
Estimated Expiration
2041-02-01

AI Technical Summary

Technical Problem

Existing geopolymer-based fireproof coatings are prone to cracking and irregular deformation when subjected to heat, which limits their suitability as lightweight fireproof materials for steel structures.

Method used

A geopolymer-based lightweight fireproof material is formulated by adding an alkaline solution to a mixture containing active and inactive fillers, lightweight fire-resistant aggregates, and a foaming agent, with specific proportions and properties to maintain strength and resist deformation at high temperatures.

Benefits of technology

The material exhibits reduced cracking and irregular deformation when heated to 1000°C, making it suitable for use as a fireproof coating on steel structures while maintaining physical and chemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602227000007
    Figure 0007602227000007
  • Figure 0007602227000008
    Figure 0007602227000008
  • Figure 0007602227000009
    Figure 0007602227000009
Patent Text Reader

Abstract

To provide a geopolymer lightweight refractory material which hardly causes a crack or irregular deformation when receiving heat.SOLUTION: A geopolymer lightweight refractory material is obtained by adding an alkaline solution to a blended material including an active filler, nonactive filler, lightweight refractory aggregate, and a foaming agent, and kneading and curing the mixture, the refractory material having density of 1.0 g / cm3 or less. The active filler is a mixture of a first active filler such as fly ash and a second active filler such as blast furnace slag fine powders, and a mass ratio of the second active filler is 10-20 mass%. The nonactive filler is not cured with the alkaline solution or, even if cured, provides compression strength of the cured body of 5 MPa or less, and maintains physical properties and chemical properties even if heated to 1000°C, and a mass ratio of the nonactive filler is 20-50 mass%. The lightweight refractory aggregate has a density of 1.65 g / cm3 or less, a ratio of a particle size of 5 mm or larger and a ratio of a particle size of smaller than 0.15 mm in the particle size distribution are respectively 0 mass% and 5 mass% or less, and a volume ratio of the lightweight refractory aggregate is 40-60 vol.% in the entire lightweight refractory material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a geopolymer-based lightweight fireproof material suitable as a fireproof coating for steel frame structures. [Background technology]

[0002] In recent years, geopolymers, which are made primarily from waste and by-products, have been attracting attention as a low-carbon binder. Geopolymers do not use cement clinker, but are made by hardening active fillers such as fly ash and ground blast furnace slag through a condensation polymerization reaction in an alkaline solution environment. 2 The emission intensity of geopolymer cement is about 20% of that of Portland cement, and that of geopolymer concrete is 30-60% of that of Portland cement concrete. For this reason, research and development of geopolymers is being actively conducted both in Japan and overseas in order to reduce the environmental impact of cement and concrete and to expand the use of waste materials. In addition, unlike the hydration reaction of Portland cement, the condensation polymerization reaction of geopolymers does not involve Ca(OH) 2 Since it does not produce crystals, it has better fire resistance and acid resistance than hardened Portland cement, and is expected to be used in high-temperature and acidic environments.

[0003] On the other hand, the Building Standards Act requires the use of fire-resistant coating materials for steel-framed structures to ensure safety in the event of a fire. Currently, cement-based fire-resistant coating materials are the mainstream, but as mentioned above, geopolymer-based fire-resistant coating materials are in demand from the perspective of waste utilization and reducing environmental impact. Lightweight fireproof coating materials are necessary. In Patent Document 1, the inventors proposed a method for foaming geopolymers, and clarified that the strength of the hardened porous geopolymer body is reduced after it is heated, and the specific strength is increased. However, the hardened porous geopolymer remains susceptible to cracking and irregular deformation when exposed to heat. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6430268 Summary of the Invention [Problem to be solved by the invention]

[0005] The problem to be solved by the present invention is to provide a geopolymer-based lightweight fireproof material that is less susceptible to cracking and irregular deformation when exposed to heat. [Means for solving the problem]

[0006] According to one aspect of the present invention, there is provided a geopolymer-based lightweight fire-resistant material comprising: The mixture contains active filler, non-active filler, lightweight fire-resistant aggregate, and foaming agent, and is mixed with an alkaline solution, kneaded, and cured to obtain a concrete with a density of 1.0 g / cm. 3 A geopolymer-based lightweight fire-resistant material, The active filler is a mixture of at least one first active filler selected from fly ash, finely ground molten slag from municipal waste incineration ash, and finely ground molten slag from sewage sludge incineration ash, and at least one second active filler selected from finely ground blast furnace slag and metakaolin, and the mass ratio of the second active filler is 10 to 20 mass% based on 100 mass% of the total amount of the active filler and the inactive filler; The inactive filler does not harden in the alkaline solution, or even if it hardens, the compressive strength of the hardened body is 5 MPa or less, and the physical and chemical properties are maintained even when heated to 1000°C. stone powder The mass ratio of the inactive filler is 20 to 50 mass% based on 100 mass% of the total amount of the inactive filler and the active filler, The lightweight refractory aggregate is Its physical and chemical properties are maintained even when heated to 1000℃. Density is 1.65g / cm 3Hereinafter, a geopolymer-based lightweight fire-resistant material in which the proportion of particle sizes of 5 mm or more in the particle size distribution is 0 mass %, and the proportion of particle sizes of less than 0.15 mm is 5 mass % or less, and when the total volume of the lightweight fire-resistant aggregate, the active filler, and the inactive filler is 100 volume %, the volume proportion of the lightweight fire-resistant aggregate is 40 to 60 volume %. Effect of the Invention

[0007] The geopolymer-based lightweight fireproof material of the present invention is less likely to crack or deform when exposed to heat, and is therefore suitable as a fireproof covering material for steel frame structures. [Brief description of the drawings]

[0008] [Figure 1] SEM photo of fly ash. [Diagram 2] SEM photo of ground granulated blast furnace slag. [Diagram 3] A photo of granular and powdered perlite. [Figure 4] Photo of fine powder of perlite raw stone and crushed stone powder. [Diagram 5] Photographs showing the process of producing hardened geopolymer foam. [Figure 6] Photographs showing a method for measuring the temperature of the back surface, which is the surface opposite to the heated surface, during a one-sided heating test. [Figure 7] Graph showing the relationship between the dimensional reduction rate after heating in a full surface heating test and the mass proportion of stone powder (inactive filler). [Figure 8] Graph showing the relationship between the density increase rate after heating and the mass fraction of stone powder (inactive filler) in a full surface heating test. [Figure 9] Graph showing the relationship between the rate of change in bending strength before and after heating in a full-surface heating test and the mass fraction of stone powder (inactive filler). [Figure 10] Graph showing the relationship between the ratio of compressive strength before and after heating in a full-surface heating test and the mass fraction of stone powder (inactive filler). [Figure 11]Graph showing the relationship between the specific compressive strength before heating and the mass fraction of stone powder (inactive filler) in a full-surface heating test (Examples only). [Figure 12A] Photographs showing the appearance of a test specimen before and after full surface heating (Example). [Figure 12B] Photographs showing the appearance of a test specimen before and after full surface heating (Comparative Example 1). [Figure 12C] Photographs showing the appearance of a test specimen before and after full surface heating (Comparative Example 2). [Figure 13] SEM photograph showing the internal structure of the hardened geopolymer foam without stone powder (non-reactive filler) and lightweight aggregate. [Figure 14] Graph showing the relationship between the density reduction rate after heating and the mass fraction of stone powder (inactive filler) in a one-sided heating test. [Figure 15A] Photographs showing the occurrence of cracks and warping in a test specimen after one-sided heating (Example). [Figure 15B] Photographs showing the occurrence of cracks and warping in a test specimen after one-sided heating (Comparative Example). [Figure 16] Graph showing the relationship between the warpage of the test specimen after one-sided heating and the mass fraction of stone powder (inactive filler). [Figure 17] Graph showing the temperature rise on the back side of a test specimen when heated on one side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The geopolymer-based lightweight fireproof material of the present invention is obtained by adding an alkaline solution to a mixture containing an active filler, an inactive filler, a lightweight fireproof aggregate, and a foaming agent, kneading the mixture, and curing the mixture. One embodiment of the material will be described below.

[0010] 1.Materials used 1.1 Active fillers JIS Class II fly ash (hereinafter referred to as "FA") was mainly used. When FA is used alone as an active filler for geopolymer (hereinafter referred to as "GP"), the setting time of GP is long in a room temperature environment and the strength development is small. Therefore, in order to increase the strength development of the GP hardened body and match the foaming speed and setting speed of GP, JIS 3000 class ground granulated blast furnace slag (hereinafter referred to as "BFS") was used in combination. If BFS is not used in combination, settlement due to expansion occurs immediately after foaming, or the foam shrinks significantly after curing. However, if the mass ratio of BFS is too high, CASH gel is generated in the hardening reaction, reducing the fire resistance of GP. Here, as mentioned above, BFS is used to increase the strength development of the GP hardened body, and metakaolin (hereinafter referred to as "MK") is also known to have the effect of increasing the strength development of the GP hardened body. Therefore, MK can be used in place of BFS or in combination with BFS. Also, while FA has a lower strength development than BFS and MK, molten slag powder from municipal waste incineration ash and molten slag powder from sewage sludge incineration ash have the same strength development as FA. Therefore, molten slag powder from municipal waste incineration ash and / or molten slag powder from sewage sludge incineration ash can be used in place of FA or in combination with FA. That is, in the present invention, the active filler is a mixture of at least one first active filler selected from FA, fine powder of molten slag from municipal waste incineration ash, and fine powder of molten slag from sewage sludge incineration ash, and at least one second active filler selected from BFS and MK. The mass ratio of the second active filler, which acts to increase the strength expression of the GP hardened body, is 10 to 20 mass% based on the total amount of the active filler and the inactive filler (hereinafter, the total amount of the active filler and the inactive filler is referred to as "powder") 100 mass%. If the ratio of the second active filler is less than 10 mass%, sufficient strength cannot be obtained. On the other hand, if the mass ratio of the second active filler is more than 20 mass%, problems such as the fire resistance of GP will decrease as described above when BFS is added, and the waste utilization effect of the present invention will decrease when MK is added will occur. In the examples of the present invention described later, the mass proportion of the second active filler, BFS, was set to 15 mass %. The chemical compositions and physical properties of FA and BFS are shown in Table 1. FA is a spherical particle with a particle size of 30 μm or less, as shown in Figure 1, while BFS is a particle with random particle size and shape, as shown in Figure 2.

[0011] [Table 1]

[0012] 1.2 Alkaline solution In the present invention, the alkaline solution may be any solution that is commonly used for producing a GP cured body, i.e., at least one selected from the group consisting of silicates, hydroxides, and carbonates of alkali metals. In the present examples and comparative examples, the alkali solution was examined in advance so that the foaming speed and the setting speed of GP were matched to increase the amount of expansion due to foaming of GP, and the strength loss after heating was not or was reduced. As a result, the commercially available sodium silicate (SiO 2 28.6% by mass, Na 2 O12.0%, molar ratio 2.5, density 1.46g / cm 3 ) and a 10M aqueous solution of caustic soda (density 1.33 g / cm 3 ) in a volume ratio of 4:1 was used as the alkaline solution.

[0013] 1.3 Aggregates In the present invention, in order to suppress shrinkage, cracking, and irregular deformation that occur in the GP hardened body when it is heated at high temperatures, lightweight refractory aggregate is added as an aggregate. Here, the "lightweight refractory aggregate" in the present invention is a lightweight refractory aggregate having a density of 1.65 g / cm 3 Hereinafter, this refers to a particle size distribution in which the percentage of particles 5 mm or larger is 0% by mass, and the percentage of particles less than 0.15 mm is 5% by mass or less. The fire resistance of lightweight aggregate means that its physical and chemical properties are maintained even when heated to 1000°C. Specifically, it means that it will not decompose or melt, its size or shape will not change, and it will not become brittle even when heated to 1000°C. When such a suitable amount of lightweight refractory aggregate is added, the lightweight refractory aggregate restrains the shrinkage of the GP matrix, so that cracks and irregular deformation due to shrinkage can be suppressed. In order to fully exert such effects, in the present invention, the lightweight refractory aggregate is added so that the volume ratio of the lightweight refractory aggregate is 40 to 60 volume % when the total volume of the lightweight refractory aggregate, the active filler, and the inactive filler is 100 volume %. If the volume ratio of the lightweight refractory aggregate is less than 40 volume %, the effect of suppressing the above-mentioned shrinkage, cracks, and irregular deformation cannot be sufficiently obtained. On the other hand, if the volume ratio of the lightweight refractory aggregate is more than 60 volume %, the strength of the GP decreases, so that cracks and irregular deformation are more likely to occur. In addition, if the volume ratio of the lightweight refractory aggregate is more than 60 volume %, even if the GP is foamed by adding a foaming agent, air bubbles leak out and it is difficult to expand, making it difficult to reduce the weight of the GP. In the examples of the present invention, granular perlite (hereinafter referred to as "granular P") was used as the lightweight refractory aggregate. The density of this granular P is 0.12 g / cm 3 The particle size distribution is >5.0 mm (0 mass%), 5.0-2.5 mm (10 mass%), 2.5-1.25 mm (43 mass%), 1.25-0.63 mm (45 mass%), 0.63-0.15 mm (1.5 mass%), <0.15 mm (0.5 mass%). In the examples of the present invention, the volume fraction of granular P is 48-50 volume%. On the other hand, in the comparative example, in addition to granular P, powdered perlite (hereinafter referred to as "powdered P") and silica sand were used as aggregates. The density of powdered P is 0.09 g / cm 3 The particle size distribution is >1.25 mm (2.0 mass%), 1.2-0.63 mm (25.0 mass%), 0.63-0.15 mm (66.0 mass%), <0.15 mm (7.0 mass%). The density of the silica sand is 2.59 g / cm 3 The particle size distribution is 0.63 mm or more (0 mass%), 0.63 to 0.315 mm (33 mass%), 0.315 to 0.15 mm (66 mass%), and <0.15 mm (1 mass%). Figure 3 shows photos of granular perlite and powdered perlite. Granular P and powdered P are made by heating and rapidly cooling raw perlite ore, and are so-called lightweight aggregates.

[0014] 1.4 Admixtures (a) Foaming agent In the present invention, a foaming agent is added to reduce the weight of the GP. As disclosed in the above-mentioned Patent Document 1, the foaming agent is metal silicon (Si), metal aluminum (Al), and hydrogen peroxide (H 2 O 2 The foaming agent may be added in an amount of 0.5 to 3 mass % based on 100 mass % of the powder. Here, in the case of strongly alkaline GP, the foaming time of metallic aluminum and hydrogen peroxide is within 10 minutes, so a special kneading and molding method is required. In contrast, the foaming time of metallic silicon is more than 30 minutes at room temperature of 20°C. Therefore, in the present examples and comparative examples, a commercially available silicon reagent (metallic silicon, density 2.33 g / cm 3 , powder size ≦150 μm, purity 95%) was used as the foaming agent. In the following description, GP that has been foamed with a foaming agent to make it porous is referred to as "GP foamed hardened material."

[0015] (b) Foam stabilizer Strongly alkaline GP has a fast foaming reaction rate, which easily leads to the formation and escape of large bubbles, and the distribution of the bubbles is easily non-uniform. This reduces the final expansion amount of the GP, and the generation of large interconnected voids reduces the insulation properties and strength. Therefore, in the present examples and comparative examples, commercially available zinc stearate (density 1.09 g / cm) was used as a foam stabilizer to reduce the size of the bubbles and improve the uniformity of the bubble distribution. 3 ) was added. In the present invention, the addition of a foam stabilizer is not essential, but it is preferable to add a foam stabilizer for the reasons described above. As the foam stabilizer, in addition to the above-mentioned zinc stearate, dodecylbenzenesulfonate, triethanolamine, etc. can be added, and the addition ratio can be 0.5 to 2 mass% based on 100 mass% of the powder.

[0016] (c) Inactive filler (stone powder) When GP is heated, dehydration (bound water) of the raw material occurs, causing cracks due to shrinkage. Therefore, in the present invention, a part of the active filler is replaced with an inactive filler. Here, the "inactive filler" in the present invention is one that does not harden in the above-mentioned alkaline solution, or if hardened, the compressive strength of the hardened body is 5 MPa or less, and even if heated to 1000 ° C, the physical properties and chemical properties are maintained. In the present invention, the inactive filler is used so that the mass ratio of the inactive filler is 20 to 50 mass % in 100 mass % of the powder. If the mass ratio of the inactive filler is less than 20 mass %, the effect of suppressing cracks due to shrinkage cannot be sufficiently obtained. On the other hand, if the mass ratio of the inactive filler exceeds 50 mass %, the mass ratio of the active filler is reduced accordingly, and the strength of the GP is reduced. Since the inactive filler is a substitute for the active filler, there is no restriction on its size, but it is preferable that it is the same as or slightly larger than the active filler, and expressed in terms of specific surface area, is 2000 to 4000 cm. 2 It is preferable that the molecular weight is about 1 / g. As an inactive filler, limestone powder, which is easily decomposed by heating, cannot be used, and typically siliceous stone powder can be used. In the present examples and comparative examples, two types of stone powder were used: perlite raw stone fine powder (hereinafter referred to as "PP") made by pulverizing perlite raw stone in a ball mill, and crushed stone powder (hereinafter referred to as "CSP"). Note that CSP is a waste product discharged during the production of crushed stone and crushed sand. Figure 4 shows photos of the two types of stone powder, and Table 2 shows the chemical compositions of the two types of stone powder.

[0017] [Table 2]

[0018] 2. Preparation of GP foam cured body The mixing method was as follows: all materials except for the alkaline solution (active filler, aggregate, stone powder, foaming agent, foam stabilizer) were mixed in a mortar mixer for 3 minutes, then the alkaline solution was added and mixed for another 2 minutes. As shown in Figure 5(a), the formwork was filled to about half capacity with the sample, and immediately subjected to vibration compaction using a table vibrator for 30 seconds. The specimen was then placed in a drying box at 80°C without being removed from the formwork. Foaming was completed after about 1 hour (see Figure 5(b)). After foaming was completed, the specimen was removed from the drying box and the excess part higher than the formwork was cut off as shown in Figure 5(c). The specimen was then removed from the formwork, sealed with plastic wrap, and cured at high temperature for the specified time, and then cured again sealed for 27 days in an atmosphere at 20°C and 60% RH. A 4x4x16cm rectangular column specimen was used for the full-surface heating test, and a 20x20x3cm flat plate specimen was used for the one-sided heating test. The flat plate specimen was also used for measuring thermal conductivity.

[0019] 3. Heating method and performance test At 28 days of age, the surface condition of the specimens was photographed, and the dimensions, bulk density, bending strength, compressive strength, and thermal conductivity were measured. In the strength test, three 4 x 4 x 16 cm rectangular column specimens were used to measure bending strength using a universal testing machine with a three-point method. In addition, the compressive strength of the six broken pieces after the bending test was measured using a universal testing machine. In addition, the thermal conductivity before heating was measured using the heat flow meter method (HFM method) using 20 x 20 x 3 cm flat plate specimens. Heating tests were conducted on the remaining specimens. A small electric heating furnace was used for the full surface heating test, which heated the entire surface of the specimen. The temperature was raised in the electric furnace at a rate of 5°C / min, and the temperature was raised to 1000°C and maintained for 5 hours. After that, the specimens were allowed to cool naturally in the furnace. After cooling to room temperature, the same measurements were conducted as before heating. In the single-sided heating test, in which one side of the specimen was heated, a flat plate specimen measuring 20 x 20 x 3 cm was heated on one side to 945°C in an electric furnace for one hour according to the standard heating curve of ISO834. During single-sided heating, a thermocouple was attached to the back side, the opposite side to the heated side, to monitor the temperature of the back side, as shown in Figure 6. After single-sided heating and cooling, the dimensions, bulk density, and warpage of the flat plate specimen were measured, and the crack conditions on the heated side and back side were photographed. The length and width of the flat plate specimen were measured at the midpoint in the thickness direction. The thermal conductivity of a part of the heated flat plate specimen after heating was also measured using the HFM method described above. The moisture state of the specimens before the heating test was either air-dried (air-dried state) or bone-dry (absolutely dry state). The air-dried specimens were 28 days old, and the bone-dry specimens were 28-day old air-dried specimens that were dried at 100±5℃ for one day.

[0020] 4. Mixing of GP foam hardener Table 3 shows the formulation of the GP foamed cured material subjected to the full-surface heating test, and Table 4 shows the formulation of the GP foamed cured material subjected to the one-sided heating test. In Tables 3 and 4, "mass ratio" refers to the mass ratio (mass%) in 100% mass of powder (BFS+FA+stone powder), "volume ratio" refers to the volume ratio (volume%) when the total volume of powder (BFS+FA+stone powder) and aggregate is 100% by volume, "addition ratio" refers to the percentage (mass%) in terms of the total mass of powder (BFS+FA+stone powder). Also, "mass ratio of alkaline solution to powder" refers to the mass of alkaline solution / mass of powder (BFS+FA+stone powder).

[0021] [Table 3]

[0022] [Table 4]

[0023] In the formulation of the examples, the mass ratio of CSP was 20-40 mass%, the mass ratio of BFS was 15 mass%, and the mass ratio of granular P was 8 mass%. As a result, the volume ratio of granular P was 48-50 volume%. In the comparative examples, GP foamed hardened bodies were produced without adding stone powder, aggregate, or BFS, or with the addition of powdered P or silica sand. In the formulation of the examples and comparative examples, the addition ratio of the foaming agent and foam stabilizer was appropriately adjusted depending on the temperature when the test specimen was produced. The moisture state of the specimens before performance measurement and heating was air-dried or bone-dry. The high-temperature curing time of the specimens measured in the air-dry state was 12 hours, while the high-temperature curing time of the other specimens was 24 hours.

[0024] 5. Test results and discussion 5.1 Full surface heating test Table 5 shows the changes in dimensions, density and strength before and after the full surface heating test.

[0025] [Table 5]

[0026] When the GP foam hardened material was heated to 1000°C, the dimensions decreased and the density and compressive strength increased. In particular, the compressive strength after heating was 1.3 times or more that before heating. Regarding bending strength, there were both comparative example and example specimens in which the bending strength decreased after heating compared to before heating. This is because the distribution and dimensions of cracks that occurred before and after heating greatly affected the bending strength, and there was variation in the bending strength of the specimens. Figure 7 shows the relationship between the mass percentage of stone powder and the rate of dimensional reduction after heating, without distinguishing between different types of stone powder. As the figure shows, the higher the mass percentage of stone powder, the less the dimensional change after heating. Also, Figure 8, which shows the relationship between the mass percentage of stone powder and the rate of density increase after heating, shows that the density change after heating is smaller as the mass percentage of stone powder increases. Therefore, it can be said that adding an appropriate amount of stone powder has the effect of suppressing dimensional change caused by heating of GP foamed hardened body. In addition, the relationship between the mass fraction of stone powder and the rate of change in bending strength after heating is shown in Figure 9. Although there was some variation, the higher the mass fraction of stone powder, the greater the rate of increase in bending strength after heating. Similarly, as shown in Figure 10, the ratio of compressive strength after heating to before heating increased with an increase in the mass fraction of stone powder. Since cracks have a significant effect on the strength of the hardened body, these results suggest that the higher the mass fraction of stone powder, the greater the effect of suppressing cracking caused by heating. However, according to Figure 11, the specific compressive strength before heating tended to decrease with the mass fraction of stone powder. In other words, by increasing the mass fraction of stone powder, the strength of the GP foamed hardened body after heating can be increased, but excessive addition reduces the strength before heating.

[0027] Even in the case of the test specimens in the examples, the dimensional change after full heating is somewhat large. Also, the bending strength before heating is not high. This is because part of the active filler is replaced with stone powder, which is an inactive filler. However, if fibers are added as in conventional molded plate fireproof coating materials, the dimensional change in each direction can be suppressed to 1% or less even when heated on the entire surface, and bending strength can be improved.

[0028] Figures 12A to 12C show the occurrence of cracks and irregular deformation in each specimen after it was subjected to full heating at 1000° C. As shown in Figure 12A, in the example of the present invention in which the mass fraction of CSP was 20 to 40 mass % and the volume fraction of granular P was 48 to 50 volume %, almost no cracks or irregular deformation occurred in the specimen. On the other hand, in Comparative Examples 4, 7, and 11, in which granular P was not added, Comparative Example 5, in which CSP was not added, Comparative Example 6, in which the mass ratio of PP was low at 6 mass%, and Comparative Example 8, in which powdered P was added instead of granular P, cracks and warping were confirmed to occur after heating. When the GP foamed hardened material is heated to 1000℃, the NASH gel and CASH gel, which are incomplete products of the condensation polymerization reaction, are dehydrated and decomposed, melted and sintered, resulting in a decrease in volume (see Figure 13). This decrease in volume is thought to be the main cause of cracks and irregular deformation. On the other hand, when a suitable amount of stone powder and granular P is added, a framework structure is formed inside the GP foamed hardened body by these inactive fillers and granular refractory aggregates. That is, a refractory particle skeleton (refractory particle skeleton structure) having a continuous particle size from small particles to large particles is formed from the small inactive filler particles and the relatively large lightweight aggregate particles, and the product of the condensation polymerization reaction of the active filler is filled into the gaps of this particle skeleton. And, due to the skeleton effect of this skeleton structure, even if the condensation polymerization reaction product shrinks due to thermal decomposition, the shape and dimensions of the entire system do not change, so it is thought that cracks and irregular deformation of the GP foamed hardened body do not occur. From the viewpoint of forming a refractory particle skeleton structure having a continuous particle size, it is preferable that the lightweight refractory aggregate used in the present invention has a continuous particle size rather than a single particle size.

[0029] On the other hand, when ordinary sand or silica sand is added as aggregate, the volume fraction of aggregate is low, for example, as in Comparative Example 9, because ordinary sand and silica sand have a high specific gravity. In that case, the sand particles are separated, and the framework structure due to the intertwining of particles described above is not sufficiently obtained. In addition, if the amount of sand added is increased, the sand hinders the foaming and expansion of the GP paste, and the density of the sand itself is high, so a lightweight GP foamed hardened body cannot be obtained. In addition, when powdered aggregate is added, for example, in Comparative Example 8, the volume fraction of powdered P is 55.2 volume%, but the dimensions of the aggregate are small, so the framework effect described above is not sufficiently obtained. For this reason, it is considered that cracking and irregular deformation of the GP foamed hardened body after heating could not be suppressed in Comparative Examples 8 and 9.

[0030] When an inactive filler that does not decompose, melt, or deteriorate when heated to 1000°C, such as stone powder, is not added (Comparative Example 5), a continuous particle framework structure from fine particles to large particles is not formed regardless of the addition of lightweight aggregate. Similarly, when the mass ratio of stone powder is low, as in Comparative Example 6, a continuous particle framework structure is not formed due to a lack of fine particles. Therefore, it is considered that the GP paste between the granular aggregate shrinks significantly when heated at high temperatures, causing cracks and irregular deformation in the GP foamed hardened body.

[0031] In addition, when BFS is used together with FA as an active filler, the strength of the GP foamed cured body using only FA as an active filler is improved because BFS produces CASH gel in a condensation polymerization reaction. Therefore, the use of BFS in combination is effective in increasing the strength of the GP foamed cured body. However, compared with NASH gel, which is a product of the condensation polymerization reaction of FA, the fire resistance of CASH gel, which is a product of the condensation polymerization reaction of BFS, is low. Therefore, the mass ratio of BFS is preferably 10 to 20 mass% or less. The specimen of Comparative Example 10, which was not used in combination with BFS, had low strength before heating, and warped after heating, and many cracks occurred. This is considered to be due to the low strength of the GP foamed cured body and low resistance to shrinkage and cracking. In addition, it was confirmed that the specimen of Comparative Example 10 sunk after foaming and expansion because the strength development was slow.

[0032] 5.2 One-sided heating test Table 6 shows the changes in dimensions, density and thermal conductivity before and after the one-sided heating test, as well as the warpage after the one-sided heating test.

[0033] [Table 6]

[0034] The dimensions after one-sided heating were reduced in the same way as in the case of full-sided heating, but the reduction rate was smaller than in the case of full-sided heating. In the case of the examples, the reduction rates of the length and width dimensions were mostly less than 1.0%, and the reduction rate of the volume was less than 5.0%. Regardless of the specimens of the examples and comparative examples, the bulk density was reduced from before heating, contrary to the case of full-sided heating. This was because the volume reduction rate was smaller compared to the degree of mass reduction after one-sided heating. As shown in Figure 14, the higher the mass ratio of stone powder, the smaller the reduction rate of density tends to be. This is because when a large amount of stone powder is added, the volume reduction rate after one-sided heating is smaller, or the mass reduction of the GP paste is smaller.

[0035] The thermal conductivity of some of the test specimens was measured after heating. Comparing the thermal conductivity measured before and after heating, it was found that the thermal conductivity after heating increased when the density before heating was low, but decreased when the density before heating was relatively high. This is because, as shown in Figure 13, when the GP foam cured body is heated, it melts, sinters, and becomes porous. As the body becomes porous, the thermal conductivity of the GP foam cured body decreases. However, when the density before heating is very low, the internal voids become interconnected and expand after heating, making it easier for thermal convection to occur, and it is thought that the thermal conductivity instead increases.

[0036] 15A and 15B show the crack occurrence state before and after heating on the heated surface and the reverse surface, and the measured value of the warpage after heating. In Examples 1 to 3 of the present invention, in which the mass ratio of CSP is 20 to 40 mass% and the volume ratio of granular P is 48 to 50 volume%, almost no cracks occurred on the heated surface and the reverse surface of the test specimen, and the maximum warpage was about 2.5 mm. In contrast, in Comparative Examples 4 to 11, cracks occurred on the heated surface and the back surface, and large warping occurred on the side (mostly 2.5 mm or more). In particular, many cracks occurred on the heated surface, making it almost impossible to continue using the specimen after heating. In Comparative Example 9, in the case of full surface heating, cracks and irregular deformation did not occur much as shown in FIG. 12C, but in the case of one-sided heating, cracks occurred and warping was large. This is probably because the surface area-volume ratio of the plate-shaped specimen in the case of one-sided heating is large compared to the square column specimen in the case of full surface heating, and the silica sand particles with a small volume fraction are too dispersed, reducing the skeletal effect. In addition, as shown in FIG. 16, although there is variation in the occurrence and measurement of warping, the higher the mass fraction of stone powder, the smaller the warping after one-sided heating tends to be. However, as mentioned above, considering the specific strength before heating, it is not preferable to greatly increase the mass fraction of stone powder, and it is preferable to keep it at 50 mass% or less. Furthermore, as described above, by adding fibers or reinforcing materials to the GP foamed cured product of the embodiment, the dimensional change of the GP foamed cured product after one-sided heating can be further reduced, and the occurrence of cracks and irregular deformation after heating can be completely suppressed.

[0037] Figure 17 shows the temperature rise on the backside of the specimens of the Examples and Comparative Examples in a one-sided heating test. Compared to the Comparative Examples, the maximum temperature was slightly lower in the Examples, and the rate of temperature rise (gradient of the curve or inclination of the rising stage) was smaller. The temperature rise was particularly fast in Comparative Examples 9 and 11, which did not use silica sand or granular P. Furthermore, the temperature rise in Comparative Example 10, where no BFS was added, was faster and the maximum temperature was higher than in Example 2, which was formulated in the same way except for the addition of BFS. As described above, it was found that the addition of BFS and the use of stone powder and lightweight refractory aggregate improve the thermal insulation properties of GP foamed hardened body or at least have no adverse effects.

[0038] 6. Summary The test results above can be summarized as follows: When GP foam hardened body is heated to 1000℃, it becomes porous and its dimensions and volume decrease. When the entire surface is heated, the volume decreases more and the density increases, but when one side is heated, the volume decreases less and the density after heating decreases. In addition, due to melting and sintering, the compressive strength increases after heating. When the density before heating is small, the thermal conductivity after heating increases, but when the density before heating is relatively large, it decreases. When the GP foamed hardened body is not added with an appropriate amount of lightweight fire-resistant aggregate and non-active filler, it shrinks significantly after heating, causing irregular deformation, which leads to cracks. On the other hand, when the lightweight fire-resistant aggregate and the heat-stable non-active filler are added in an appropriate amount, the lightweight GP foamed hardened body can be produced without any problems, and the non-active filler and the lightweight fire-resistant aggregate form a particle framework structure with continuous particle size, which suppresses the shrinkage of the GP foamed hardened body due to heating, and prevents cracks and irregular deformation. It is generally known that the bending strength can be increased by further adding heat-resistant fibers and reinforcing materials, and cracks and irregular deformation due to heating can be completely prevented. In order to achieve both strength and fire resistance of the GP foamed cured material, the mass ratio of BFS is preferably 10 to 20 mass%. Since the condensation polymerization reaction product of MK is NASH gel, the same as FA, even if the mass ratio of MK is high, it does not affect the fire resistance of the GP foamed cured material, but from the viewpoint of mass utilization of waste, it is also recommended that the mass ratio of MK be 10 to 20 mass%.

Claims

1. The mixture containing active filler, non-active filler, lightweight refractory aggregate and foaming agent is mixed with an alkaline solution, kneaded and cured to obtain a concrete with a density of 1.0 g / cm 3 A geopolymer-based lightweight fire-resistant material, The active filler is a mixture of at least one first active filler selected from fly ash, finely ground molten slag from municipal waste incineration ash, and finely ground molten slag from sewage sludge incineration ash, and at least one second active filler selected from finely ground blast furnace slag and metakaolin, the mass ratio of the second active filler being 10 to 20 mass% based on 100 mass% of the total amount of the active filler and the inactive filler; The inactive filler does not harden in the alkaline solution, or even if it hardens, the compressive strength of the hardened product is less than 5 N / mm 2 The stone powder has a physical property and a chemical property that are maintained even when heated to 1000°C or less, and the mass ratio of the inactive filler is 20 to 50 mass% based on 100 mass% of the total amount of the inactive filler and the active filler, The lightweight refractory aggregate maintains its physical and chemical properties even when heated to 1000°C and has a density of 1.65 g / cm 3 Hereinafter, a geopolymer-based lightweight fireproof material in which the proportion of particle sizes of 5 mm or more in the particle size distribution is 0 mass %, the proportion of particle sizes of less than 0.15 mm is 5 mass % or less, and when the total volume of the lightweight fireproof aggregate, the active filler, and the inactive filler is 100 volume %, the volume proportion of the lightweight fireproof aggregate is 40 to 60 volume %.

2. 2. The geopolymer-based lightweight fireproof material according to claim 1, wherein the alkaline solution is at least one selected from the group consisting of silicates, hydroxides and carbonates of alkali metals.

3. The geopolymer-based lightweight fireproof material according to claim 1 or 2, wherein the foaming agent is at least one selected from metal silicon, metal aluminum, and hydrogen peroxide.

Citation Information

Patent Citations

  • Bipolar transistor and manufacture thereof

    JP1989030268A

  • Forming inorganic composition

    JP1996026845A

  • Porous geopolymer hardened body

    JP2016135723A

  • Self-expanding geopolymer composition containing aluminum dross

    JP2016534964A